2014
DOI: 10.1097/hjh.0b013e328365b29c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Doppler renal resistive index

Abstract: The Doppler-derived renal resistive index has been used for years in a variety of clinical settings such as the assessment of chronic renal allograft rejection, detection and management of renal artery stenosis, evaluation of progression risk in chronic kidney disease, differential diagnosis in acute and chronic obstructive renal disease, and more recently as a predictor of renal and global outcome in the critically ill patient. More recently, evidence has been accumulating showing that an increased renal resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 35 publications
(36 reference statements)
1
44
0
2
Order By: Relevance
“…Currently, clinical studies have shown that detection of subtle changes in RI were associated with renal vascular tone during sepsis, acute kidney injury and stage of chronic kidney disease in patients with renal allograft [9, 11]. Additionally, RI could be used for the management of hypertensive patients [20]. In experimental studies, the adaptation of renal RI to facilitate detailed renal injury has been limited, primarily because of technical difficulties in imaging mice versus humans, including the small size of mice, the high heart rates of small animals, and the high speed for data acquisition and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical studies have shown that detection of subtle changes in RI were associated with renal vascular tone during sepsis, acute kidney injury and stage of chronic kidney disease in patients with renal allograft [9, 11]. Additionally, RI could be used for the management of hypertensive patients [20]. In experimental studies, the adaptation of renal RI to facilitate detailed renal injury has been limited, primarily because of technical difficulties in imaging mice versus humans, including the small size of mice, the high heart rates of small animals, and the high speed for data acquisition and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Duplex waveforms of the main, segmental, interlobar and arcuate arteries were assessed in the upper, mid and lower poles in both kidneys and peak systolic velocity, end diastolic velocity and resistive indices were measured simultaneously with GFR and RPF measurements. Renal resistive index was calculated as [(peak systolic velocity-end diastolic velocity)/peak systolic velocity] 20 . Two repeated measurements were taken from each renal artery; renal resistive index of each artery was reported as the mean value of these two measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, an increased RRI has been demonstrated to predict the onset of diabetes mellitus in patients with primary HT [8,10,12,13].…”
Section: Introductionmentioning
confidence: 99%